Phytochemical, antioxidant, and enzyme inhibition potential exploration of Nyctanthes arbor-tristis via in vitro and in silico methods - Parajuli, Nirmal; Neupane , Prabhat; Dhital , Sujan; Bharati , Samjhana; Shrestha, Timila; Maharjan , Binita; Marasini , Bishnu Prasad; Subin, Jhashanath Adhikari; Shrestha , Ram Lal Swagat (Eclética Química, 2025)
Secondary metabolites in medicinal plants have been found to possess a broad spectrum of therapeutic properties. This study investigates the sequential extraction, quantitative phytochemicals, and bioactivity evaluations of Nyctanthes arbor-tristis leaf growing in Nepal. Methanolic extract contains the highest phenolics and resulted in the lowest IC50 values of 56±3 µg/mL and 157±3 µg/mL, in antioxidant and α-amylase inhibition assays, respectively. Hexane extract was found to contain abundant flavonoids and to be the most lethal to brine shrimp napuili with LC50 of 87±5 µg/mL. Phytochemicals arborside-C (ASC) and arborside-D (ASD) were found to be the most potent ligands to bind with α-amylase (PDB ID: 4GQR), resulting from docking and molecular dynamics simulation outcomes. The free energy changes calculated by the MMPBSA method and ADMET profiling of hit candidates supported by the spontaneity of complex formation reactions and their pharmacokinetic efficacy, respectively. This study proposes two compounds as hit candidates for the α-amylase target. Biological characterization using an in vivo approach is further recommended to assess their precise pharmacological validation.